Measuring and Motivating Quantity, Creativity, or Both - KACHELMEIER, STEVEN J.; REICHERT, BERNHARD E.; WILLIAMSON, MICHAEL G. (Journal of Accounting Research, 2008)
ABSTRACT We examine how worker productivity differs when compensation is based on quantity, creativity, or the product of both measures. In an experiment in which participants design “rebus puzzles,” we find that combining quantity and creativity measures in a creativity‐weighted pay scheme results in creativity‐weighted productivity scores that are significantly lower than those generated by participants with quantity incentives alone. Follow‐up analysis indicates that relative to participants in the quantity‐only condition, participants in the creativity‐weighted condition produce approximately the same number of high‐creativity puzzles, but produce significantly fewer puzzles overall. Thus, while participants rewarded for creativity‐weighted output tend to restrict their production to high‐creativity efforts, they are unable to translate this focus into a greater volume of high‐creativity output. Implications address a possible explanation for firms' reluctance to incorporate creativity measures within multidimensional performance measurement systems, notwithstanding published suggestions to do so.